Common Written Errors Of English Departement Student in IKIP PGRI Bojonegoro. - Chyntia Heru Woro Prastiwi (Jurnal Pendidikan Edutama, 2014)
Common Written Errrors of English Department Students in IKIP PGRI Bojonegoro. Writing is still considered to be the most difficult skill to master as it combines ideas getting, grammatical structures, vocabulary, and mechanics. Producing good written English is an essential and required skill for English Department Students. This study examines the common errors in written English produced by the students of English Department in IKIP PGRI Bojonegoro. The error analysis on writing aims at giving the English teacher or lecturer data about common written errors and arousing the students to be more confident and enthusiastic in producing good writing by giving them correction symbols. Data were collected from narrative and descriptive texts written by the students of class 2C of English Department in IKIP PGRI Bojonegoro. The errors are analyzed in ten categories which use ten correction symbols, they are: 1) S (spelling), WO (word order), G (grammar), T (tense), C (concord), ! (missing things), WW (wrong word), [ ] (unnecessary things), ?M (unclear meaning), and P (punctuation). The overall results indicate that the most errors the students made were grammar mistakes and unnecessary things. On the contrary, the students made the least errors in word order. It was also found that the students made errors in the rest categories including spelling, tenses, concord, missing things, wrong words, unclear meaning, and punctuation.Key words: common errors, written English, correction symbols, descriptive qualitative.